Effect of the Pyrotechnic Disc on the Efficiency of theThermal Cell - N. Alkhateeb, Ahmed; H. Hussein, Falah; D. Omran, Kareem; M. Sarhan, Waleed (Asian Journal of Chemistry, 2010)
The effect of the composition of the assembled pyrotechnic disc upon the efficiency of the thermal cell was investigated by using mixtures of different percentages of the fuel, Fe and the oxidizing agent. In addition, the effect of the activating fuels including Mg, Al and Zr has also been studied. The results showed that, in the absence of the activating fuel, the mixture composed of 88% Fe and 12% KClO4 was the most active, where it gave a voltage of 1.82 V at 58 s. This result is referred to the increment in the thermal disc glow, which gave the least heat content leading to the high voltage, 1.82 V. The results also demonstrate that using activating fuels such as Mg, Al or Zr led to some slight explosions and detonations, which gave rise to irregularity of the disc ignition. Among these, Zr was found to be the best. Extended study of different mixtures composing the assembled pyrotechnic discs, that is, 85–89% Fe and variable proportions of KClO4 and Zr, disclosed that a mixture containing Fe 88%, KClO4 10% and Zr 2% was the most favourable one, which led to a glow time of 5 s. The voltage was found to be 2.27–2.30 V at 128–130 s, which was 1.82 V at 58 s, in the absence of Zr. The thermal scanning of the mixture revealed that the mixture had the heat content and entropy at 302.6ºC of 10.452 J.g–1 and 0.0180 J.g.K–1, respectively. These results were obtained to be very close to that observed with the imported pyrotechnic disc, where the heat content and entropy at 305.88ºC were 10.423 J.g–1 and 0.0181 J.g.K–1, respectively.